2017
DOI: 10.1016/j.molmet.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

KLK5 induces shedding of DPP4 from circulatory Th17 cells in type 2 diabetes

Abstract: ObjectiveIncreasing plasma levels and activity of dipeptidyl peptidase-4 (DPP4 or CD26) are associated with rapid progression of metabolic syndrome to overt type 2 diabetes mellitus (T2DM). While DPP4 inhibitors are increasingly used as anti-hyperglycemic agents, the reason for the increase in plasma DPP4 activity in T2DM patients remains elusive.MethodsWe looked into the source of plasma DPP4 activity in a cohort of 135 treatment naive nonobese (BMI < 30) T2DM patients. A wide array of ex vivo, in vitro, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 51 publications
0
48
0
Order By: Relevance
“…Levels of both membrane-bound DPP-4 protein and plasma DPP-4 enzymatic activity are altered in several pathophysiological states, including cancer, inflammation, infections, immune disorders, type 2 diabetes, and kidney disease [28,31]. The increased levels of soluble DPP-4 in type 2 diabetes seem to be at least partly derived from proteolytic processing of membrane-bound DPP-4 by kallikrein-related peptidase 5 on circulating CD4 + T helper (Th)17 cells [40].…”
Section: Dpp-4 In Kidney Disease: Active Agent or Benign Bystander?mentioning
confidence: 99%
“…Levels of both membrane-bound DPP-4 protein and plasma DPP-4 enzymatic activity are altered in several pathophysiological states, including cancer, inflammation, infections, immune disorders, type 2 diabetes, and kidney disease [28,31]. The increased levels of soluble DPP-4 in type 2 diabetes seem to be at least partly derived from proteolytic processing of membrane-bound DPP-4 by kallikrein-related peptidase 5 on circulating CD4 + T helper (Th)17 cells [40].…”
Section: Dpp-4 In Kidney Disease: Active Agent or Benign Bystander?mentioning
confidence: 99%
“…Shedding of membrane CD26 has been widely recognized on various cell types, such as human adipocytes, vascular smooth muscle cells (VSMCs), and peripheral blood mononuclear cells (PBMCs) . Several matrix metalloproteinases (MMPs) mediate the membrane CD26 shedding on adipocytes and VSMCs .…”
Section: Discussionmentioning
confidence: 99%
“…Several matrix metalloproteinases (MMPs) mediate the membrane CD26 shedding on adipocytes and VSMCs . Kallikrein‐related peptidase 5 (KLK5) also plays roles in the shedding of CD26 on human PBMCs; the CD26 shedding from PBMCs is significantly inhibited by treatment with a KLK5 inhibitor, while treatment with recombinant KLK5 has the opposite effect, dramatically inducing CD26 shedding from CD4 + T cells …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in their studies, DPP4 secretion from adipocytes and smooth cells was not impacted by brefeldin A treatment. Nargis et al recently reported an alternative mechanism whereby kallikrein-related peptidase 5 (KLK5) was shown to mediate enzymatic cleavage of DPP4 from the surface of IL-17-producing CD4 + T helper type 17 (Th17) cells [52]. Thus, the mechanism of DPP4 secretion may be tissue-dependent and additional biochemical analysis of activated lymphocytes may provide additional insights.…”
Section: Discussionmentioning
confidence: 99%